Romiplostim for Immune Thrombocytopenia in Neuroblastoma Patients Receiving Chemotherapy. Issue 4 (May 2019) - Fassel, Hannah; Bussel, James B.; Roberts, Stephen S.; Modak, Shakeel
Abstract : Thrombocytopenia, a serious complication of myelosuppressive chemotherapy in cancer patients, is managed with platelet transfusions until recovery of platelet counts. However, children receiving chemotherapy can rarely develop immune thrombocytopenia (ITP) that is refractory to transfused platelets. This limits the ability to achieve adequate platelet counts and administer further myelosuppressive chemotherapy safely, especially if first-line ITP therapy is ineffective. We report 2 cases of intravenous immunoglobulin refractory ITP in children receiving chemotherapy for high-risk neuroblastoma. ITP was successfully treated with the thrombopoietin-receptor-agonist romiplostim, allowing safe and timely continuation of antineuroblastoma therapies in these high-risk patients.